Magnetocaloric effect and spontaneous magnetization in perovskite manganite Nd0.55Sr0.45MnO3. (January 2016) - Xu, Lisha; Fan, Jiyu; Zhu, Yan; Shi, Yangguang; Zhang, Lei; Pi, Li; Zhang, Yuheng; Shi, Daning
Abstract : Graphical abstract: Abstract : Highlights: Magnetic entropy change of magnetic ceramic Nd0.55 Sr0.45 MnO3 has been studied. The paramagnetic-ferromagnetic phase transition was verified to be second-order. Spontaneous magnetization can be calculated from magnetic entropy change. Abstract: In this paper, we have investigated the magnetocaloric effect in perovskite manganite Nd0.55 Sr0.45 MnO3 . The maximum magnetic entropy change and the highest relative cooling power under magnetic field variation of 3.0 T are found to be 3.12 J/kg K and 70.87 J/kg, respectively. Based on the obtained magnetic entropy change under different magnetic fields, we have calculated the spontaneous magnetization which persistently increases with the decrease of temperatures. For comparison, the spontaneous magnetization has been also deduced from the Arrott plot. The excellent agreement between the two methods confirms that the utilization of magnetic entropy change to get the spontaneous magnetization is valid. Besides, we also calculated the critical exponent β which value is about 0.452, indicating that the observed ferromagnetic phase transition in the present material can be approximatively understood with mean field model.